2014
DOI: 10.1186/0717-6287-47-17
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and biochemical characterization of egg extract of black widow spiders to uncover molecular basis of egg toxicity

Abstract: BackgroundBlack widow spider (L. tredecimguttatus) has toxic components not only in the venomous glands, but also in other parts of the body and its eggs. It is biologically important to investigate the molecular basis of the egg toxicity.ResultsIn the present work, an aqueous extract was prepared from the eggs of the spider and characterized using multiple physiological and biochemical strategies. Gel electrophoresis and mass spectrometry demonstrated that the eggs are rich in high-molecular-mass proteins and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 41 publications
2
13
0
Order By: Relevance
“…Besides, analysis of cellular component indicated that the identified proteins were distributed in various parts of the cell, including the cell interior and the cell surface (Figure 1C). These data suggest that proteins identified through the transcriptome analysis are extensively distributed in various subcellular locations of the L. tredecimguttatus eggs and involved in multiple cellular processes and biological functions, particularly in binding, catalysis, development, etc., which is in agreement with the basic functions of the eggs and the results of our previous work [14,15]. …”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…Besides, analysis of cellular component indicated that the identified proteins were distributed in various parts of the cell, including the cell interior and the cell surface (Figure 1C). These data suggest that proteins identified through the transcriptome analysis are extensively distributed in various subcellular locations of the L. tredecimguttatus eggs and involved in multiple cellular processes and biological functions, particularly in binding, catalysis, development, etc., which is in agreement with the basic functions of the eggs and the results of our previous work [14,15]. …”
Section: Resultssupporting
confidence: 93%
“…In addition, the molecular weights of the proteins in eggs are mainly distributed in the range of from about 34 kDa to above 170 kDa, with the highest abundant protein bands at around 65 kDa and 130 kDa, respectively. Besides, Yan et al [14] studied the physiological and biochemical properties of the egg extract, and the results showed that the extract could completely block the neuromuscular transmission in mouse isolated phrenic nerve-hemidiaphragm preparations and inhibit the voltage-activated Na + , K + and Ca 2+ currents in rat DRG neurons. Furthermore, the neurotoxicity of the eggs to mammals was shown to be primarily attributed to their high-molecular-mass protein components.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations